Giverny em mim: estudos poéticos a partir da obra de Claude Monet - Tinoco, Rebeca Desyre Nuan do Prado Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Artistic creation is an individual process and full of its own meanings, so this work set out to analyze Claude Monet's artistic production in a direct dialogue with his influences on my artistic production in the Giverny in me. Thus, he sought to answer the following question: How do my works of art carry the artistic references that I possess? For that, he defined as a general objective to understand how artistic processes take place in the face of artistic experience, and as specific objectives: to analyze Monet's artistic practice, mainly from Giverny, to describe how the experience of visitation in his work Ninféias Azuis influenced my practice and understand how my creative process in Giverny took place in me. So I produced my series of works, based on the study of Monet's life and work and relating it to my life and personal experiences, creating a parallel between Giverny and the city where I grew up, Guarantã. It is a post-structuralist research in art, which intends to observe the creative process and autoethnography.

A criação artística é um processo individual e repleto de sentidos próprios, assim, esse trabalho propõe-se a analisar a produção artística de Claude Monet em um diálogo direto com suas influências sobre minha produção artística na série que denominei “Giverny em mim”. Assim, busca-se responder à seguinte pergunta: Como minhas criações carregam em si as referências artísticas que possuo? Para isso, definiu-se como objetivo geral compreender como os processos artísticos ocorrem diante da experiência artística. Os objetivos específicos consistem em analisar a prática artística de Monet, principalmente a partir do local em que foi a principal referência para suas obras: Giverny; descrever como a experiência de visitação em sua obra “Ninféias Azuis” influenciou minha prática; e compreender como ocorreu o processo criativo dos trabalhos que são descritos na presente pesquisa. Assim produzi minha série de trabalhos, baseando-me no estudo da vida e obra de Monet e relacionando com minhas experiências de vida e pessoais, criando um paralelo entre a Giverny e a cidade onde cresci, Guarantã. Trata-se de uma pesquisa poética, experimental e autoetnográfica.
Giverny in me: poetic studies based on the work of Claude Monet
Keywords: Impressionism; Landscape; Water lilies; Art; Claude Monet; Impressionismo; Paisagem; Processo criativo; Artes visuais